STRATEGY TO IMPROVE INCOME OF FISHERMEN IN SULAMU VILLAGE, KUPANG REGENCY, NUSA TENGGARA TIMUR PROVINCE - Aguslan, Aguslan; Noviyanti, Rinda; Putra, Anak Agung Made Sastrawan (Aurelia Journal, 2024)
Sulamu Village is one of the villages in Kupang Regency that makes fishing activities the main livelihood of the community. Fishing efforts by the community do not have a significant impact on history, which is reflected in income. The purpose of this study is to analyze the feasibility of business, profitability and strategies to increase the income of capture fishermen. The data analysis method, namely business feasibility analysis using Revenue Cost Ratio (R/C) and Payback period (PP) analysis, business profitability analysis and SWOT analysis. The results of the analysis are that the fishing business of fishermen in Sulamu Village is profitable and feasible. This can be seen from the R/C value of each fishing gear used, which is all >1, while the payback period (PP) is >3 while the ROI is obtained with a value >1. The analysis of IFAS and EFAS is a grand strategy located in the position of growth-oriented strategy, which is a strategy that supports aggressive growth policies. The strategy implemented is to empower fishermen to actively care for the sea and SDI in the Sawu Sea, facilitate the reach of fishermen's access to capital, and fulfil infrastructure to support fishermen's activities.